Kualitas Pelayanan Publik di Kantor Kelurahan Sudiang Raya Kecamatan Biringkanaya Kota Makassar - mutmainnah; Nurlina; Nur Apriyani (WORKFORCE JOURNAL: Manajemen & Bisnis, 2026)
This study aims to determine the quality of public services, factors, and levels of public satisfaction with services received at the Sudiang Raya Village Office, specifically based on the dimensions of public service quality, namely tangibles (kenampakan fisik), reliability (keandalan), responsiveness (ketanggapan), assurance (jaminan), and empathy (empati). This study uses a qualitative approach with a descriptive case study design. Data were collected through direct observation and direct interviews with respondents. The results show that the quality of public services at the Sudiang Raya Village Office demonstrates a commitment to improvement, although not yet fully optimal, with strengths and weaknesses in the five dimensions of SERVQUAL: tangibles, reliability, responsiveness, assurance, and empathy. Physical facilities are quite adequate but need to be updated, while limited human resources hamper the speed of service even though procedures have been attempted to run well. Friendliness, professionalism, and the implementation of "smile, greet, and to address" are positive values, but their consistency is not evenly distributed. The main obstacles include the lack of facilities such as computers and printers, differences in perceptions regarding the completeness of documents, and workloads that are not commensurate with the number of employees. To improve overall quality, it is necessary to add and rejuvenate infrastructure, train staff, improve structures and management to be more responsive, digitize services, and strengthen communication and consistently socialize procedures to align expectations and the reality of service.